Beijaard's model of teachers' professional identity - Predrag Ž. Živković (University of Belgrade, Teacher Education Faculty, 2019)
The aim of the research is to use logistic regression to determine the predictive and classification values of the three-dimensional Beijaard's model of teachers' professional identity (teachers as subjectmatter experts, didactical experts, and pedagogical experts). Logistic regression as an analyticalstatistical procedure for testing this model has not been done so far. The most important results of the research are as follows: the selected set of predictor variables for each element of the criterion variable gives good results in the model; the aggregate performance indicators of the model are within the required limits; the model classifies a satisfactory percentage of cases for all three elements of the professional identity model